Gerga Orange Quality Using Naïve Bayes Based on Feature Extraction - Nugroho, Fajar Raditya; Khoirudin, Khoirudin (Universitas Dian Nuswantoro and IndoCEISS, 2023)
In an effort to increase the number of sales, the process of classifying the type of Gerga citrus fruit is very necessary. The problem that often occurs is the mixing of various types of fruit from the storage warehouse so that the quality of the fruit will be mixed and it will be difficult to determine the selling price because the quality of the fruit itself is not evenly distributed so that a sorting process is needed. There are still many sellers or growers of citrus fruits who sort the quality of the fruit manually so that it can take a very long time. Given these problems, it is necessary to classify the quality of Gerga oranges automatically with the Naïve Bayes Classifier algorithm with GLCM feature extraction and HSV color characteristics. as a method for classifying the quality of Gerga citrus fruit and as for the media used, there is digital image media. From the experiments that have been carried out the use of angles in the formation of co-occurrence matrices with the best accuracy values reaching 80% are found at angles of 0°, 45°, and 135°, while the lowest accuracy values are found at angles of 90°. It was concluded that the Gerga citrus fruit quality classification system using the Naïve Bayes method was categorized as good with an AUC value of 0.8.